Nonlinear Analysis of Return Time Series Model by Oriented Percolation Dynamic System - Anqi Pei; Jun Wang (Abstract and Applied Analysis)
Fluctuation dynamics of financial price changes is developed and investigated by oriented percolation system; oriented percolation is percolation with a special direction along which the activity can only propagate one way but not the other. Then, nonlinear behaviors of distribution and leverage effect of return time series are studied for the proposed model and the real stock market by comparison. We also investigate the scaling behaviors of return intervals. And a scaling function of exponential parameter is introduced to analyze fluctuation behaviors of return intervals. The empirical research exhibits that, for proper parameters, the simulation data of the model can fit the real markets to a certain extent.